Предмет: Алгебра,
автор: Аноним
упростите выражение (а – 9)2 + 2 (8 – 2а)
Ответы
Автор ответа:
0
(а-9)2+2(8-2а)= 2а-18+16-4а= -2а-2= -2(а+1).
Автор ответа:
0
там а-9 в квадрате
Автор ответа:
0
Упростил не до конца!
Автор ответа:
0
(а-9)^2 + 2(8-2а) =
= а^2 - 18а + 81 + 16 - 4а =
= а^2 - 22а + 97 = 0
= а^2 - 18а + 81 + 16 - 4а =
= а^2 - 22а + 97 = 0
Похожие вопросы
Предмет: Русский язык,
автор: Valeriybezpechniy
Предмет: Русский язык,
автор: sabnambabaeva83
Предмет: Английский язык,
автор: chay1243
Предмет: Математика,
автор: Аноним
Предмет: Литература,
автор: 1makwert2016